2015
DOI: 10.1002/2015jc010934
|View full text |Cite
|
Sign up to set email alerts
|

Joint assimilation of Aquarius‐derived sea surface salinity and AVHRR‐derived sea surface temperature in an ocean general circulation model using SEEK filter: Implication for mixed layer depth and barrier layer thickness

Abstract: Sea surface salinity (SSS) from Aquarius mission and sea surface temperature (SST) from Advanced Very High Resolution Radiometer (AVHRR) for the years 2012–2014 are assimilated into the global Massachusetts Institute of Technology General Circulation Model (MITGCM). Investigation of the impact of assimilation of these two data sets on simulated mixed layer depth (MLD) and barrier layer thickness (BLT) forms the core of our study. The method of assimilation is the Singular Evolutive Extended Kalman (SEEK) filte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 38 publications
(70 reference statements)
2
10
0
Order By: Relevance
“…Density changes near the surface directly impact the MLD. Figure c shows that overall shoaling of the MLD is evident between 10 °S and ~5 °N and this feature is broadly consistent with the results of Chakraborty et al () that assimilated Aquarius SSS data. This MLD shoaling is coincident with thinning of the depth of the 20 °C isotherm (a proxy for the depth of the thermocline) in Figure d such that the equatorial waveguide is much shallower than both north and south of the equator west of 120 °W and is consistent with the meridional gradient pattern of the density plot (Figure b).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Density changes near the surface directly impact the MLD. Figure c shows that overall shoaling of the MLD is evident between 10 °S and ~5 °N and this feature is broadly consistent with the results of Chakraborty et al () that assimilated Aquarius SSS data. This MLD shoaling is coincident with thinning of the depth of the 20 °C isotherm (a proxy for the depth of the thermocline) in Figure d such that the equatorial waveguide is much shallower than both north and south of the equator west of 120 °W and is consistent with the meridional gradient pattern of the density plot (Figure b).…”
Section: Resultsmentioning
confidence: 99%
“…These variances are used to construct a diagonal matrix of model errors . Since the assimilation is limited to the tropical Indo‐Pacific region, a single value is chosen for the observational error corresponding to 3 cm (Busalacchi et al, ), 0.3 °C (Chakraborty et al, ), and 0.2 psu (Lagerloef et al, ) for SL, SST, and SSS, respectively. For T z and S z , the observational error is chosen as 0.75 °C and 0.31 psu, respectively.…”
Section: Models and Data Assimilation Descriptionmentioning
confidence: 99%
See 2 more Smart Citations
“…Though, to date, the impacts shown have been somewhat minor. A number of other studies showed positive impacts due to the assimilation of SSS in controlled experiments, including improved upper ocean salinity (Vernieres et al, 2014), improved surface currents, mixed-layer depth, and barrier layer thickness (Chakraborty et al (2014(Chakraborty et al ( , 2015, and improved temporal variability of the vertical distribution of salinity in areas with large freshwater input (Seelanki et al, 2018). Still, the low temporal frequency of the data, large uncertainty estimates attributed to instantaneous observations, and large platform-specific biases (Bao et al, 2019), make the assimilation of SSS a continuing challenge.…”
Section: Prediction At Subseasonal To Seasonal Timescalesmentioning
confidence: 99%